Seizures in autoimmune encephalitis: Kindling the fire. (13th May 2020) - Wesselingh, Robb; Butzkueven, Helmut; Buzzard, Katherine; Tarlinton, David; O'Brien, Terence J.; Monif, Mastura
Abstract: Epilepsy is a common neurological disorder that increases the risk of morbidity and mortality. Autoimmune epilepsy is a subset of epilepsy that occurs in the setting of autoimmunity, such as in autoimmune encephalitis (AIE). AIE is an autoimmune disorder characterized by immune‐mediated neuroinflammation resulting in a variety of neurological symptoms, including psychiatric disturbance, cognitive dysfunction, and seizures. Seizures in AIE are thought to be a result of antibodies directed against neuronal cell‐surface proteins involved in synaptic transmission. The role of blood‐brain barrier dysfunction, myeloid cell infiltration, and the initiation of proinflammatory cascades in epileptogenesis has been shown to be important in animal models and human patients with epilepsy. Epileptogenesis in AIE is likely to arise from the synergistic effect of both innately driven neuroinflammation and antibody‐induced hyperexcitability. Together, these processes produce persistent drug‐resistant seizures that contribute to the morbidity seen in AIE. Understanding the proinflammatory pathways involved in this process may improve diagnostics and provide alternative treatment targets in AIE.